Advanced logistics planning for offshore wind farm operation and maintenance activities. (1st June 2015) - Dalgic, Yalcin; Lazakis, Iraklis; Dinwoodie, Iain; McMillan, David; Revie, Matthew
Abstract: Offshore wind turbine technology is moving forward as a cleaner alternative to the fossil fuelled power production. However, there are a number of challenges in offshore; wind turbines are subject to different loads that are not often experienced onshore and more importantly challenging wind and wave conditions limit the operability of the vessels needed to access offshore wind farms. As the power generation capacity improves constantly, advanced planning of Operation and Maintenance (O&M) activities, which supports the developers in achieving reduced downtime, optimised availability and maximised revenue, has gained vital importance. In this context, the focus of this research is the investigation of the most cost-effective approach to allocate O&M resources which may include helicopter, crew transfer vessels, offshore access vessels, and jack-up vessels. This target is achieved through the implementation of a time domain Monte-Carlo simulation approach which includes analysis of environmental conditions (wind speed, wave height, and wave period), operational analysis of transportation systems, investigation of failures (type and frequency), and simulation of repairs. The developed methodology highlights how the O&M fleets can be operated in a cost-effective manner in order to support associated day-to-day O&M activities and sustain continuous power production. Highlights: The cost of jack-up vessel related activities is higher than cost of other activities. The second half of the year can be too late to start preventive maintenance tasks. It is unlikely to complete preventive maintenance without separate O&M technicians. Helicopter is an important aspect due to its different operational characteristics. The total O&M cost can be decreased by selecting the most favourable O&M plan.